Advanced Study on Drying Kinetics and Mathematical Modeling of Bottle Gourd - Ingle, Murlidhar; Tapre, A. R.; Nawkar, Radhika (New Ideas Concerning Science and Technology Vol. 5, 2021)
Aims: Bottle gourd (Lagenaria siceraria L.) is an important vegetable crop of tropical and sub-tropical regions of the world belonging to family Cucurbitaceae. It is most popular in Indo-Pakistan sub-continent and cultivated throughout India. The aim of this study was to evaluate the drying behavior of bottle gourd slices using tray dryer. Study Design: The bottle gourd slices were dried in a tray dryer at 50, 55, 60, 65 and 70 + 1°C. The moisture loss was determined by gravimetry. Readings were taken at 30 minutes till constant weight was observed. Place and Duration of Study: Experiments were done in Department of Food Science and Technology, MPKV Rahuri and completed within 12 months. Methodology: The drying curves were fitted into four different drying models (Henderson, Logarithm, Page and Modified Page) widely accepted for modeling of agricultural materials drying. The best model describing the drying process was selected based on the low RMSE, low ?2, and high R2. Results: The drying time at 50, 55, 60, 65 and 70ºC drying temperature were 630, 570, 450, 420 and 360 min respectively for bottle gourd slices. By comparing time required at 50ºC and 60ºC temperature and 60ºC and 70ºC there were 28.57% and 20.00% reduction in drying time respectively. At the beginning of a drying process, the moisture content of fresh bottle gourd was 92.09% (w.b.) which is reduced to 7.08% (wb). The drying rate decreased with increase in drying time. The drying rates were as high as 0.89 at 55ºC and as low as 0.1 at almost all the temperatures. The R2 values ranged from 0.788 to 0.954, the adjusted R2 values also ranged from 0.777 to 0.951, ?2 values between 0.029 and 0.681, and RMSE values between 0.0533 and 0.3742. Conclusion: Increased in air drying temperature decreased the drying time. Drying mostly occurred in the falling rate period. Henderson and Pabis model was found to be a better model for describing the drying characteristics of bottle gourd at all temperatures. The product quality was found well at all the temperature.